2018
DOI: 10.14569/ijacsa.2018.090819
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Acceptance of Mobile Health Application User Interface Cultural-Based Design to Assist Arab Elderly Users

Abstract: Mobile health (m-health) applications are a way to provide solutions to the non-availability of physical health services in the Arab world. However, end users of m-health around the world have their cultural and personal differences that distinguish them from others. Studies suggest that culture is an essential component of the success of any product or technology usage. In view of this, the study investigated acceptance towards mobile health application User Interface (UI) designed for Arab elderly users base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 40 publications
(43 reference statements)
0
28
1
Order By: Relevance
“…In addition, Ahmed ALsswey et al . (2018 a ) reported that language is one of the most vital cultural aspects that reflect the identity of societies which may positively influence users' acceptance of a system. Thus, the use of Arabic language in the design of UI was due to its role in enhancing the acceptance and satisfaction of users when interacting with the display.…”
Section: Ui Design Componentsmentioning
confidence: 99%
“…In addition, Ahmed ALsswey et al . (2018 a ) reported that language is one of the most vital cultural aspects that reflect the identity of societies which may positively influence users' acceptance of a system. Thus, the use of Arabic language in the design of UI was due to its role in enhancing the acceptance and satisfaction of users when interacting with the display.…”
Section: Ui Design Componentsmentioning
confidence: 99%
“…Behavioral intention to use health applications which is interpreted as an individual's desire to continually access and interact with health applications as well as using it is the goal of this study (Deng et al, 2018). The behavioral intentions maker to use the application are influenced by attitudes (Tran 2016;ALsswey et al, 2018;Askari et al, 2020). Attitude as a mediating variable is influenced by perceived usefulness, perceived ease of use, social influence, feelings of anxiety, and service availability (Mhina et al, 2019;Askari et al, 2020;Sezgin et al, 2018;Kamal et al, 2020).…”
Section: Behavioral Intentionmentioning
confidence: 99%
“…Individuals get benefit from online health applications that provide health information and physician consulting services. It makes their better condition (Shareef et al, 2014;ALsswey et al, 2018). Useful perception positively affects individual attitudes towards online health applications because the more perceived benefits made.…”
Section: Useful Perceptionmentioning
confidence: 99%
“…Previous studies have shown a shift in Arab culture towards a preference for meetings via mobile phones (ALsswey et al, 2018;Ameen and Willis, 2018a). Hence, this factor can affect both intention and usage of smartphones and mobile applications.…”
Section: Culture-specific Beliefs and Values (Csbv)mentioning
confidence: 99%